Germany Democratic Republic and Polish National Republic political polices - Woycicki, Kazimierz (Genocidas ir rezistencija, 2006)
The Soviet regime needed to establish security structures in the satellite states. Due to the weak satellite communist parties (further weakened by Stalin’s repression), the Soviet regime had no confidence in its allies. In Poland, there was a widespread public opposition and the extremely weak Communist government; hence, the Soviet mistrust is understandable. East Germany was a defeated and hated enemy. It only regained statehood and partial independence in 1949, although the foundations of its security structures had already been laid after 1945. Between 1944 and 1953, the security services of both countries fought real and perceived enemies. There are similarities and differences between these structures. Similarities include subordination to the Communist Party; the development of a prison system promoted by the political police; physical repression during the Stalinist period; and the heavy financial burden on the budget. Similarities were due to the Soviet example and influence. The most important similarity between the political police in the two countries was their impotence in containing the growing mass grassroots movement. The differences were as follows: the Stasi apparatus was constantly expanding, and in the People's Republic of Poland the political police had serious internal and staffing problems. The number of Stasi informers was constantly growing, whereas in Poland this number fluctuated. East Germany had much greater possibilities to put pressure on people, while in Poland there were several social institutions that played a key role in defending the persecuted. The Stasi staff were fully prepared to fulfil their mission, while the secret police in communist Poland was consistently going through phases of ‘moral corruption’.
Keywords: Poland; Germany; repressive structures; resistance; terror; agents